PENGARUH BRAND IMAGE DAN COUNTRY OF ORIGIN TERHADAP KEPUASAN DAN LOYALITAS KONSUMEN PADA PRODUK TV SAMSUNG DI SURABAYA - ABDI, YONATHAN TEDJA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The purpose of this study was to test brand image and country of origin to satisfaction and customer loyalty on samsung tv product in Surabaya. In this research, predicted that those two independent variables could measure satisfaction and customer loyalty as dependent variables.This study using SEM analysis to analyze brand image and country of origin to satisfaction and customer loyalty. while sampling in this study using purposive sampling method so the samples that used in this study has 150 respondent. This study concluded that brand image and country of origin can affect customer satisfaction and customer loyalty. Brand image significantly influence consumer satisfaction, country of origin significant effect on customer satisfaction, and customer satisfaction significantly influence customer loyalty.